Genetics of Primary Adrenal Insufficiency Beyond CAH in Saudi Arabian Population - Mohamed H. Al‐Hamed; Alya Qari; Lamya Alrayes; Mohammed Alotaibi; Zainab Al Masseri; Afaf Alotaibi; Abdullah AlAshwal; Zuhair N. AlHassnan; Afaf Alsagheir (Molecular Genetics & Genomic Medicine)
ABSTRACT Background The use of exome sequencing (ES) has helped in detecting many variants and genes that cause primary adrenal insufficiency (PAI). The diagnosis of PAI is difficult and can be life‐threatening if not treated urgently. Consanguinity can impact the detection of recessively inherited genes. Here, we report families with PAI in a consanguineous population of Saudi Arabia. Materials and Methods A cohort of 47 PAI patients (41 males and six females) representing 30 families was recruited. The cohort excluded congenital adrenal hyperplasia (CAH) cases and had a known consanguinity of 70%. Using ES, molecular genetic causes of PAI were investigated. Results In 30 unrelated families with PAI, pathogenic/likely pathogenic variants were detected in 27 families with a diagnostic yield of (90%). Clinically associated variants of uncertain significance (VUS) were identified in a further two PAI families (7%). Hemizygous variants in ABCD1 were the most common cause of PAI in this cohort (16 families) leading to adrenoleukodystrophy. A total of six novel variants were detected, of which four were predicted to be pathogenic (P) / likely pathogenic (LP) and two were VUS. Four pathogenic variants in ABCD1, NR0B1, and MC2R were detected in 10 families suggesting founder mutations. Conclusion In this cohort, ES detected a diagnostic molecular abnormality in 90% of patients with PAI phenotypes. X‐linked inheritance is the most common cause of PAI and founder mutations likely contributed to a high diagnostic yield.